Kairos der Barmherzigkeit. Barmherzigkeit als Prinzip einer missionarischen Seelsorge - Polak, Mieczysław (Poznańskie Studia Teologiczne, 2015)
The pastoral care of the church needs a paradigm, on which it can build its practice. This paradigm must take signs of the contemporary times into account. The message of mercy was crucial for the pontificates of John XXIII, John Paul II and Benedict XVI. Mercy is also an essential theme of teaching for Pope Francis. The primary sign of the contemporary times is mercy. At times we are called to gaze even more attentively on mercy so that we may become a more effective sign of the Father’s action in our lives (Pope Francis). The main issue of the present article is mercy as a paradigm of the missionary and pastoral care of the church. Three statements create the issues for this study: pastoral ministry in a missionary key, contemporary times as the times of mercy and principles and areas of the pastoral of the mercy.